Aproximações em torno da zona muda das representações sócias de ciclos de aprendizagem entre professores - Laeda Bezerra Machado (Universidade Estadual de Campinas, 2012)
This article identifies the likely area change of social representations of learning cycles for teachers in city of Recife-PE. The text is based on the structural approach of social representations. 52 teachers participated in the survey of public schools. We used as data collection instrument replacement technique, a variation of the open interview, which called for an assertive professional to comment on the issue cycles. The data were interpreted using content analysis. The results suggest a zone change that rejects the cycles of learning cycles implemented in public schools, mainly due to the end of the retention of students recommended by it. The existence of a regularity of negative content present in the speech of teachers helps us understand the reasons for adopting this new form of school organization is not giving rise to a democratization of the educational situation of school in the country as a right of citizenship. Thus, we assume that educational policies, while promising, faced with the social representations of teachers.